A Semiautoregression Approach to the Arbitrage Pricing Theory. - Mei, Jianping (Journal of Finance, 1993)
This paper develops a semiautoregression approach to estimate factors of the arbitrage pricing theory that has the advantage of providing a simple asymptotic variance-covariance matrix for the factor estimates, which makes it easy to adjust for measurement errors. Using the extracted factors, the author confirms the finding that the arbitrage pricing theory describes asset returns slightly better than the capital asset pricing model, although there is still some mispricing in the arbitrage pricing theory model. The author finds that not only are the factors priced by the market, but the factor premiums move over time in relation to business cycle variables.